UTILIZING ENGLISH SONGS TO IMPROVE STUDENTS’ LISTENING SKILL - Sukendra, Irmala; Nuraini, Hery; Fadlilatunni’mah, Via (JIPIS, 2024)
Listening is one of the four basic skills that students must master before learning a foreign language. According to Elmetaher (2021) listening can be a challenge because listening is a complex process. In addition, students have difficulties in listening English. The teacher should be found an appropriate learning strategy to improve students’ listening skills. Therefore, the research aims to determine the significant improvement of utilizing English songs to improve students' listening skills. Songs can create more interesting learning atmosphere. The populations of the research were tenth grade in one of the senior high schools in Tangerang and the samples were 30 students in the experimental class and 30 students in the control class. The research used quasi-experimental design. The writers used pre-test and post-test in each class to get the data. The writers used multiple choice test with three indicators contained. The indicators were word perception, word recognition, and comprehension. The collected data were analyzed by using independent sample t-test. The result of this research is there is a significant improvement. In conclusion, utilizing English songs can improve students' listening skills.